EU – A Stronger Global Actor: New Contexts for EU-Korean Relations - Hak Je Yu; Cornelia Alexandra Lincan; Elena-Adina Voicilă (CES Working Papers, 2018)
European Union (EU) is currently confronting a series of challenges to its internal dynamics as well as its position on the international arena. However, EU continues to rely on its normative power in order to influence international order and build on its image as a strong global order. Our research therefore aims to contribute to the debate on the concept of Normative Power Europe, by analysing EU-Korea relations. In this manner, the framework emphasizes EU's role as a global actor, in three main areas of interest for both strategic partners: economy and trade, development cooperation, peace and security. As such, the main findings revolve around maintaining a sound cooperation in the three areas analysed – and reflect, on one side, a strengthening of the “global actor” main trait of the EU, and on the other side, a consolidation of Korea's position in world politics.
Keywords: 330; development aid; European Union; Korea; normative power; peace talks